Handbook of Applied Solid State Spectroscopy - Vij, D.R.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
Solid-State spectroscopy is a burgeoning field with applications in many branches of science, including physics, chemistry, biosciences, surface science, and materials science. Handbook of Applied Solid-State Spectroscopy brings together in one volume information about various spectroscopic techniques that is currently scattered in the literature of these disciplines. This concise yet comprehensive volume covers theory and applications of a broad range of spectroscopies, including NMR, NQR, EPR/ESR, ENDOR, scanning tunneling, acoustic resonance, FTIR, auger electron emission, x-ray photoelectron emission, luminescence, and optical polarization, and more. Emphasis is placed on fundamentals and current methods and procedures, together with the latest applications and developments in the field.
NUCLEAR MAGNETIC RESONANCE SPECTROSCOPY -- NUCLEAR QUADRUPOLE RESONANCE SPECTROSCOPY -- ELECTRON PARAMAGNETIC RESONANCE SPECTROSCOPY -- ENDOR SPECTROSCOPY -- MÖSSBAUER SPECTROSCOPY -- CRYSTAL FIELD SPECTROSCOPY -- SCANNING TUNNELING SPECTROSCOPY (STS) -- RESONANCE ACOUSTIC SPECTROSCOPY -- FOURIER TRANSFORM INFRARED SPECTROSCOPY -- AUGER ELECTRON SPECTROSCOPY -- X-RAY PHOTOELECTRON SPECTROSCOPY -- LUMINESCENCE SPECTROSCOPY -- LASER-INDUCED FLUORESCENCE SPECTROSCOPY -- SOFT X-RAY EMISSION AND RESONANT INELASTIC X-RAY SCATTERING SPECTROSCOPY -- LASER RAMAN SPECTROSCOPY -- POLARIZATION SPECTROSCOPY OF ORDERED SAMPLES.
Keywords: Spectroscopy; Microscopy; Solid state physics; Materials science; Spectroscopy and Microscopy; Solid State Physics; Spectroscopy/Spectrometry.; Characterization and Evaluation of Materials